Decolorization of synthetic azo dyes under anaerobic condition in a continuous stirred tank reactor - Mohamad Adib Syahmi Latif; Fazilah Ariffin; Rudiyanto; Shahrul Ismail; Noorazrimi Umor; Abu Zahrim Yaser; Zaharah Ibrahim (Journal of Pure and Applied Microbiology, 2021)
Biological treatment for textile wastewater always has a limitation in term of time of reaction and uncertainty along the process. This study focused on the decolorization of synthetic azo dyes in batch reactors with controlled thermotolerant anaerobic conditions. Less-volatile digested sludge collected from a palm oil biogas reactor was used as the organic biodegradation agent for azo dyes. Digested sludge contains high amounts of microbes with uncertain species viable for decolorization purposes. Sodium acetate trihydrate (C2 H9 NaO5 ) was used as carbon source and mixed with a specific composition of minimum salt media (MSM) in batch reactors as an additional nutrient. Digested sludge both in mesophilic (35°C) and thermophilic (55°C) conditions were found to be capable of decolorizing 100, 200 and 300 ppm of three types of azo dyes: Reactive Green 19 (45.56%, 69.73%; 63%, 73.49%; 70.02%, 75.92%), Reactive Orange 16 (46.08%, 78.4%; 64.21%, 85.52%; 74.95%, 85.91%) and Reactive Red 120 (29.11%, 85.32%; 63.35%, 87.69%; 72.02%, 89.5%) respectively after 7 days incubation time. Statistical analysis also showed that the anaerobic thermophilic conditions had significantly accelerated the decolorization process. The anaerobic thermophilic environment will be a good factor to include in future textile wastewater treatment plants.